Does the READ Scale Work for Chat? A Review of the Literature - Warner, Adrienne; Hurley, David A. (Evidence Based Library and Information Practice, 2021)
Objective – This review aims to determine the suitability of the READ Scale for chat service assessment. We investigated how librarians rate chats and their interpretations of the results, and compared these findings to the original purpose of the Scale. Methods – We performed a systematic search of databases in order to retrieve sources, applied inclusion and exclusion criteria, and read the remaining articles. We synthesized common themes that emerged into a discussion of the use of the READ Scale to assess chat service. Additionally, we compiled READ Scale designations across institutions to allow side-by-side comparisons of ratings of chat interactions. Results – This review revealed that librarians used a variety of approaches in applying and understanding READ Scale ratings. Determination of staffing levels was often the primary goal. Further, librarians consistently rated chat interactions in the lower two-thirds of the scale, which has implications for service perception and recommendations. Conclusion – The findings of this review indicated that librarians frequently use READ Scale data to make staffing recommendations, both in terms of numbers of staff providing chat service and level of experience to adequately meet service demand. Evidence suggested, however, that characteristics of the scale itself may lead to a distorted understanding of chat service, skewing designations to the lower end of the scale, and undervaluing the service.